Analysis of the Combined Three-dimensional Wind Field Retrieved by Radar and Reanalysis Wind Field based on Optimum Interpolation Technique - Songyu HAN; Liji WANG; Lili KANG; Yongsheng LIU; Zhou TENG; Lingli ZHOU; Yefeng CHEN (Gaoyuan qixiang)
In order to construct a grid spatiotemporal continuous three-dimensional wind products integrating wind retrieved by radar， combining ERA5 reanalysis wind field which used as the first-guess field and three-dimensional wind field retrieved by dual-radar networking which used as the observed field based on optimal interpolation technique.The error statistics of the ERA5 reanalysis and radar retrieved wind fields are defined based on the data of six precipitation processes in the Zhejiang region and the error structures were employed to compute the weights， the combined hourly three-dimensional wind field with 0.25°×0.25° resolution were obtained as the final results which checked and evaluated with the second radio-sounding wind data.The results show that： Compared with the ERA5 wind field， the accuracy of the combined wind field is improved， root mean square error is reduced by 6% （U component）， 16% （V component）； the correlation coefficient is increased by 0.02 （V component）.The combined wind field has effectively corrected the rather smaller wind field shown by the reanalysis data near the eye of typhoon Lekima， filled the blind area of radar retrieval wind field， and formed a complete and accurate wind field product， corrected the large deviation of the typhoon location with ERA5 wind field.Combined with the small-scale wind information retrieved by radar， the combined wind field reflects the original inconspicuous convergence characteristics of ERA5 wind field， and improves the application value of data.